Studied on Physico-Chemical Characteristics and Lipid Profile of Bittergourd (Momordica charantia) Oil - Sharma, P.B. (Asian Journal of Chemistry, 2010)
Momordica charantia (bittergourd) seed oil was evaluated for oil content, physico-chemical characteristics and tatty acid composition. High iodine value (144), R.InD40 (1.4960) and acetyl value (59%) of this dark-brown coloured oil indicated high degree of unsaturation. The acid and peroxide values were within normal limits. R.M. and P. values showed that the lower volatile fatty acids were present to a small extent. Low unsaponifiable matter (1%) and sap. value (208) were comparable to conventional oils like groundnut and sesame. Bittergourd oil like other cucurbit seed oils has palmitic-stearic-oleic-Iinoleic type fatty acid composition. In addition, it possessed high level of conjugated α-eleostearic acid (50%) as revealed by GLC and UV spectrum studies..